Association of a genetic variant (rs689466) of Cyclooxygenase-2 gene with chronic periodontitis in a sample of Iraqi population - Dahash, Suha A.; Mahmood, Maha Sh. (Journal of Baghdad College of Dentistry, 2019)
Background: periodontitis is a chronic inflammatory disease causing destruction of the tooth supporting structures, initiated by dental plaque and modified by environmental and genetic risk factors. Cyclooxygenase-2 (COX-2) enzyme is responsible for the production of prostaglandin E2, an important mediator in the chronic periodontitis (CP) pathogenesis. Polymorphisms in COX-2 gene have linked to CP in different populations. Aim: To study the association between Cyclooxygenase-2 single nucleotide polymorphism rs689466 (-1195A/G SNP) and chronic periodontitis in a sample of Iraqi population. Methods: One hundred Iraqi subjects divided into two groups: case group consisted of 70 CP patient (35 males and 35 females) with age range 30-55 years, and control group consisted of 30 racially matched healthy subjects (15 males and 15 females) with age range 30-50 years. Clinical periodontal parameters including plaque index (PLI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL) were recoded for all participants. 3ml of venous blood was collected from each participant for isolating genomic DNA. Genotyping of the rs689466 in COX-2 gene was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Results: The frequency of G allele carriers was significantly more prevalent in the case group compared to control group (P= 0.041), and allele G was associated with greater susceptibility for chronic periodontitis compared to allele A (OR=1.4). Conclusion: COX-2 (rs689466) polymorphism may be associated with increased chronic periodontitis susceptibility.